Merry Christmas cowboy - Yates, Maisey (Yates, Maisey. Four Corners Ranch, 2022)
Cowboy Wolf Garrett is delighted his brother is happily married. But time can never heal Wolf's own wounds, so being surrounded by such marital joy is a bit much. A trip to his extended family's ranch in Copper Ridge seems the ideal change of scenery. Until he meets local innkeeper Violet Donnelly and realizes he's exchanged one form of torture for another, trying, and spectacularly failing, to resist their instant, wildly hot chemistry.